REPOSISI CITRA MNC TV DALAM MEMBENTUK REBRANDING IDENTITY SEBAGAI TELEVISI DANGDUT DI INDONESIA (STUDI KASUS PROGRAM KDI DI MNC TV) - Annory langga o (Jurnal Penelitian Sosial Ilmu Komunikasi, 2023)
Along with the Times and technology, companies engaged in products, especially event programs. Required to always develop, attract and innovate. Companies will compete to make corporate identity or corporate image good to the community. The impression created starts from making typical programs or flagship programs in a television station which will make the company's image and brand identity known to the public as corporate identity.TPI itself is already known as dangdut television in Indonesia, where TPI made the biggest dangdut singer Talent Search Program at that time, before competitors made similar programs. From 2004 to 2009. Approximately 6 years, the KDI program has aired on TPI. Until where TPI changed its name to MNC TV in 2010, the KDI (Indonesian dangdut contest) Program aired again in 2010 to 2022. The problem in this study is how to reposition the image of MNC TV in continuing the KDI program (Indonesian dangdut contest) by forming a rebranding identity as dangdut television in indonesia the purpose of this study is to determine how MNC TV forms a rebranding identity as dangdut television in Indonesia by continuing the KDI program (Indonesian Dangdut contest) which focuses on the KDI program (Indonesian Dangdut contest) in 2018, by adding similar programs. This research uses constructivist paradigm and presented qualitatively. Data collection techniques used are case studies, by observing, interviewing and literature studies on news contained in company documentation, websites and mass media. The theory used is the theory of image and Rebranding theory. The results of the study were that the image of TPI at that time produced a good rating but not comparable with the existing income and there was no change in the scheme of interesting programs in airing KDI programs on TPI while the repositioning of the image of MNC TV now airs similar programs to support the repositioning of the image of MNC TV itself due to the change of name. It is undeniable that MNC TV's big name by rebranding the KDI program which focuses on 2018 using the same concept but making differences such as stage arrangement, lighting, sophisticated equipment, bigger and attractive prizes and bringing in more competent judges. Indications of the success of repositioning the image and rebranding of the KDI 2018 program on MNC TV is one of the many advertising revenues and seen from the number of contestants who participated in the KDI program (Indonesian Dangdut Contest ) 2018. As well as articles that contain MNC TV as the home of dangdut television.Keywords: MNC TV, Rebranding Identity, Repositioning, image,TPI, program KDI